Densities and Viscosities of Ionic Liquid with Organic Solvents - Fuxin Yang; Peng Feng (Applied Sciences, 2020)
The ionic liquid (IL) of 1-hexyl-3-methylimidazolium acetate is widely used in chemical and bio-chemical processes. In this work, due to the high viscosity of IL, the promising chemicals (i.e., N, N-dimethylacetamide, N, N-dimethylformamide, and dimethyl sulfoxide) were selected as the additives to lower IL viscosity. The thermophysical properties of density and viscosity for IL with solvents were measured using a digital vibrating U-tube densimeter and an Ubbelohde capillary viscometer from 303.15 to 338.15 K at atmospheric pressure (0.0967 MPa), respectively. The influences of the solvents on the thermophysical properties of ionic liquid were quantitatively studied. Furthermore, based on the measurement values, the derived properties of excess molar volumes, thermal expansion coefficient, and the energy barrier were calculated, and the results showed that the mixture composition had great impact on excess volume change and viscosity. The hard-sphere model was employed to reproduce the viscosity. The infrared spectroscopy was performed to study the chemical structure to further understand the interactions between IL and the solvents.